2004
DOI: 10.1590/s0036-46652004000600008
|View full text |Cite
|
Sign up to set email alerts
|

Strain differentiation of Trichophyton rubrum by random amplification of polymorphic DNA (RAPD)

Abstract: SUMMARYTrichophyton rubrum is an important cause of dermatomycoses. Molecular strain typing methods have recently been developed to address questions about epidemiology and source of relapse following treatment. This report describes the application of RAPD for molecular strain differentiation of this fungus utilizing the primers 1-(5'-d[GGTGCGGGAA]-3') and 6-(5'-d[CCCGTCAGCA]-3'). A total of five RAPD patterns were observed among 10 strains of T. rubrum, with each of the primers used. We conclude that RAPD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 14 publications
(7 reference statements)
0
24
2
Order By: Relevance
“…However, Jackson et al have recently reported on intraspecific variability within T. rubrum by PCR-amplifying two tandemly repetitive subelements (TRSs), located in the non-transcribed spacer (NTS) region of the rRNA gene cluster [15]. More recently, the RAPD analysis performed by Baeza et al with two decameric primers, designated 1 and 6, has been shown to produce a high degree of interstrain polymorphism [7, 16]. The RAPD analysis with primers 1 and 6 was also applied in the present study, and this choice was motivated by a high discriminatory potential of the method, higher than that of the TRS typing system [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Jackson et al have recently reported on intraspecific variability within T. rubrum by PCR-amplifying two tandemly repetitive subelements (TRSs), located in the non-transcribed spacer (NTS) region of the rRNA gene cluster [15]. More recently, the RAPD analysis performed by Baeza et al with two decameric primers, designated 1 and 6, has been shown to produce a high degree of interstrain polymorphism [7, 16]. The RAPD analysis with primers 1 and 6 was also applied in the present study, and this choice was motivated by a high discriminatory potential of the method, higher than that of the TRS typing system [16].…”
Section: Discussionmentioning
confidence: 99%
“…It yielded 40 profiles, whereas RAPD with primer 6 resulted in only five profiles (GDRs of 72.7% and 9.1%, respectively). In the first study that used primers 1 and 6, among ten clinical isolates of T. rubrum , five molecular patterns were observed for each primer [7]. In a subsequent study including 67 T. rubrum isolates, a total of 12 and 11 individual patterns were obtained by RAPD with primers 1 and 6, respectively (GDRs of 17.9% and 16.4%, respectively) [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies of dermatophytic infections have now entered a new era, due to the ability to differentiate strains of fungi by molecular typing [2,5,6,16,17]. By using molecular methods, the existence of multiple strains of T. rubrum in only one affected nail was shown and it was also found that a nail fragment containing fungal elements from more than one strain can develop into a single colony [2].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of recurrent post-treatment onychomycosis, information obtained by strain fingerprinting would determine whether the original isolate has been responsible, or a new strain has been acquired or even if multiple strains are involved in the condition [5,6]. The discrimination achieved by random amplified polymorphic DNA analysis and restriction analysis of the mitochondrial DNA is generally adequate for species identification, but is insufficiently sensitive for strain differentiation of T. rubrum isolates [3,7].…”
Section: Introductionmentioning
confidence: 99%